Study of Selected Environmental Factors Influencing extension personnel in communicating improved Animal Husbandry Practices - Raj Kamal P J (Department of Extension, College of Veterinary and Animal Sciences, 1979)
The objectives of the study were to understand the working conditions of the personnel engaged in animal husbandry extension with regard to selected environmental factors and to explore the relationship, if any, existing between the perception of the selected environmental factors by the extension personnel and their self-assessment on their role in the 'Change agent-Client system contact'. The study was conducted in Trichur taluk with all the 60 personnel engaged in animal husbandry extension work. These personnel comprised of Village Extension Officers, Livestock Assistants, Dairy Farm Instructors and Veterinary Surgeons. Results revealed that for majority of the Village Extension Officers the 'Guidance and supervision', 'Services and supplies' and 'Job satisfaction' were only 'some-what satisfactory' and below, while for factors like 'People's participation', 'Interpersonal relations and 'Communication', the environment was 'some-what satisfactory' and above. Livestock Assistants were in general not satisfied with 'Guidance and supervision', 'Services and supplies','Communication' and 'Job satisfaction'; 'some-what satisfied' with 'People's participation' and 'satisfied' with 'Interpersonal relations'. Most of the Dairy Farm Instructors expressed the existence of 'some-what satisfactory' environment on factors like 'Guidance and supervision', 'Services and supplies', 'People's participation', 'Communication' and 'Job satisfaction'. They were quite satisfied with their 'Interpersonal relationship'. For majority of Veterinary Surgeons, all the six environmental factors appeared to be 'some-what satisfactory'. Livestock Assistants had an entirely different perception of the environmental factors leaning more towards total dissatisfaction when compared to other categories in the study. There was almost unanimous agreement by all categories of personnel to the unsatisfactory nature of 'Services and supplies' prevailing in the diffusion of animal husbandry innovations and also in their 'Job satisfaction'. It was found that in the self-assessment of the extension personnel's contacts with clients the environmental factors studied had least importance in the case of Village Extension Officers and some importance in the case of Livestock Assistants and Veterinary Surgeons. The results thus indicate the necessity to improve upon the efficiency of the existing administrative machinery. It also suggests the need for a more detailed study of the working environment prevailing in the projects and organisations engaged in livestock development.